Predicting the Economic Feasibility of Implementing the Technologies of Discretly Distributed Shock Loads on Order to Decrease Drilling Accidents - Чарковський, В. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
The causes of physical deterioration of shock vibration action devices have been described to eliminate jamming of BHA during drilling. Various factors of physical deterioration of some structural node devices embedded in BHA are reflected in the formula for determining the economic efficiency. The conditions of zero efficiency for the device that implements the technology of distributed discrete shock have been determined. Input values for calculation of the payback period have been determined. EIt has been established that for effective practical implementation of the technology of distributed discrete-shock technology it is necessary to extend the application of appropriate devices by creating a special design supporting-centering elements. The necessity of the application of modeling techniques of discounting in the calculation of economic effect oas been proven.